In Vitro Hepatic Models to Assess Herb-Drug Interactions: Approaches and Challenges - Hlengwa N.; Masilela C.; Mtambo T. R.; Sithole S.; Naidoo S.; Machaba K. E.; Shabalala S. C.; Ntamo Y.; Dludla P. V.; Milase R. N. (MDPI AG, 2023)
A newfound appreciation for the benefits of herbal treatments has emerged in recent decades. However, herbal medication production still needs to establish standardized protocols that adhere to strict guidelines for quality assurance and risk minimization. Although the therapeutic effects of herbal medicines are extensive, the risk of herb-drug interactions remains a serious concern, limiting their use. Therefore, a robust, well-established liver model that can fully represent the liver tissue is required to study potential herb-drug interactions to ensure herbal medicines' safe and effective use. In light of this, this mini review investigates the existing in vitro liver models applicable to detecting herbal medicines' toxicity and other pharmacological targets. This article analyzes the benefits and drawbacks of existing in vitro liver cell models. To maintain relevance and effectively express the offered research, a systematic strategy was employed to search for and include all discussed studies. In brief, from 1985 to December 2022, the phrases "liver models", "herb-drug interaction", "herbal medicine", "cytochrome P450", "drug transporters pharmacokinetics", and "pharmacodynamics" were combined to search the electronic databases PubMed, ScienceDirect, and the Cochrane Library.